Heimatrecht und Staatsbürgerschaft österreichischer Juden Vom Ende des 18. Jahrhunderts bis in die Gegenwart - Burger, Hannelore (2014)
The study describes the process of gradual inclusion of the Jews into the ,Heimatrecht' and citizenship in the Austrian monarchy since the Josephine reforms. The stony path of integration of the Jews into general citizenship which spans centuries and is marked by numerous setbacks allows to shed new light on the act of expatriation of the Austrian Jews during the Nazi regime.The stony path of integration of the Jews into general citizenship spans many centuries and is marked by numerous setbacks. It stretches from special royal protection of the Jews ('Judenregal') via Tolerance or 'Familienstelle' all the way to full citizenship. A description of this development allows to shed new light on the previously dimly lit act of expatriation of the Austrian Jews during the Nazi regime. This was a complex process running in several stages which, although similar to the rest of the German Reich, occurred at a somewhat later stage and already under the sign of flight and expulsion. However, the disenfranchisement and - literally and legally - depersonalization of the Austrian Jews was - so the argument - not just an act of targeted Nazi persecution, but the systematic reversal in rapid motion of the Jews' emancipation which had started at the end of the 18th century. What at first glance appears to have been an abstruse and cluttered convolution of Nazi regulatory activity turns out, on closer analysis, to have been a meticulous reversal of the historical process of 'Jewish emancipation'. Numerous case studies and three major biographical studies towards the end of the book show to what extent the 'Heimatrecht' and citizenship or, by contrast, the fate of statelessness determined the lives and identities of people - far beyond the time of the Austrian monarchy.